KKN Pemberdayaan terhadap Masyarakat menuju Desa yang Inovatif dan Kreatif serta Sosialisasi Kebersihan Lingkungan dan Pemanfaatan Sampah Rumah Tangga - Sianturi, Nurli Dian Stefani; Ahiraf, Shidqul Azaim; Hidayatulloh, Syarif; Pramudya, Bintang; Fadillah, Muhammad Arief; Akbar, Fadhel Virgiawan; Dhivari, Danang; Putra, Firmansyah; Sitinjak, Jerico; Prasetyo (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Real Work Lectures (KKN) are community empowerment activities by students as an embodiment of the tridharma activities of higher education. KKN activities aim to enable students to implement science and technology as well as skills in society so that they can become agents of change and sustainable development. The participation of KKN students in community activities plays an important role in the success of work program activities while at the KKN location. This participation can be demonstrated by involving oneself directly in several activities such as fogging activities, activities to sort waste that can be recycled, socialization of diligent savings and creativity for PAUD and Kindergarten children, and tilapia fish hatchery activities. Bhayangkara University Jakarta Raya with its vision, namely